Locating thin dykes using wavelet analysis of their magnetic anomalies. Issue 5 (3rd September 2019) - Cooper, G.R.J.
ABSTRACT: The wavelet transform is a well-known tool for the multiscale processing of geophysical data. Previous work has shown how it also could be used as a semi-automatic interpretation method for potential field data. This article demonstrates how to reduce the noise-sensitivity of the method when used in this manner, by using wavelets based on analytic signal amplitudes of different orders, and by using Hilbert transforms rather than horizontal derivatives. Although both the first horizontal derivative and the Hilbert transform of a data set change its phase by 90°, because Hilbert transforms do not boost the high-frequency component of a data set the method is less sensitive to noise. The method is applied to aeromagnetic data from the Cradle of Humankind, South Africa, with geologically reasonable results.